Perancangan sistem pembangkit kogenerasi pada pabrik gula kapasitas 4.000 tcd, studi kasus revitalisasi pabrik gula modjo sragen - Ari Wibowo (Jurnal Teknik Mesin Indonesia, 2016)
The sugar industry is an industry that supplies its own energy, in which energy is generated from burning biomass in the form of bagasse to produce electricity and steam. This system is referred to as a cogeneration system, meaning the generation of two different forms of energy together from one main energy source. By designing the right generating system, sugar mills have the potential to generate electrical energy greater than the internal requirement, so the excess power that can be transfered into PLN electricity network. The purpose of this research is to design the equipment in cogeneration steam generation system with reference to the energy potential contained in bagasse. The results showed by calculation and design of equipment, the energy potential from the bagasse of 381.818.182 kJ / hour which can produce steam in the boiler as much as 100.000 kg / hour at a pressure of 45 barg 400oC. Than the turbine and generator can convert into electrical energy of 11 MW.